Software testing : a self-teaching introduction - Chopra, Rajiv (Mercury Learning and Information, 2018)
"This overview of software testing provides key concepts, case studies, and numerous techniques to ensure software is reliable and secure. Using a self-teaching format, the book covers important topics such as black, white, and gray box testing, video game testing, test point analysis, automation, and levels of testing. Includes end-of-chapter multiple-choice questions / answers to increase mastering of the topics."--Amazon.ca